Innovation ecosystem: impact of interactive patterns, member location and member heterogeneity on cooperative innovation performance. Issue 1 (2nd January 2016) - Song, Juan
Abstract : The cooperative innovation performance of an innovation ecosystem depends on the interactive activities among members of the ecosystem. This study investigates the ways in which the evolution of an innovation ecosystem, member locations, heterogeneity and the pattern of interaction among members affect cooperative innovation performance. We build an interaction model and conduct a simulation experiment and empirical research on China's railway transportation equipment industry. On the basis of a qualitative and quantitative investigation, we find that the interactive strength of focal firms and their upstream partners is more beneficial to cooperative innovation performance than the interactive strength of focal firms and their downstream partners. These findings also suggest that the exit of members of an innovation ecosystem decreases cooperative innovation performance; however, the effect of the exit of upstream component partners is more significant. We conclude that both the focal and the upstream component firms have positive influential power toward the cooperative innovation performance. In addition, this study suggests that asymmetric relationships between the focal firm and upstream and downstream partners tend to have more significant impact on their cooperative innovation performance, in which a centralized interactive pattern of the ecosystem members generated higher cooperative innovation performance than the dispersed pattern.